1881
DOI: 10.1126/science.os-2.80.618
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Heat by Muscular Activity

Abstract: It is the object of physical science in the proper sense of the word, to perceive in all thte phlenomena of nature the operations ot the same tot ces, with which any two material piarticles always act p11)01n each other, when thley comiie in contact withi each Oliehcr in th'e s-'im" relations. This object has never been so clearly seen by the majority of natur.dlis's. as (luring the last (lecaide. Since that tinme a law alread(ly proved in mlechanics has )e'tn recognizedk as one al)plicable to all the events o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…4 B) but less in a contraction with stretching than one with shortening. These results were similar to those of Fenn ( 1924 ) and Fick ( 1881 ). Whereas those authors had concluded that the results indicated that physiological processes accounted for the heat and work output, Wyman produced what now appear rather contrived arguments—a variable fraction of potential elastic energy not used as work was reabsorbed during relaxation rather than appearing as heat—to support the idea that all the thermal changes could be explained by processes that were physical (i.e.…”
Section: Consequences Of Fenn’s Papersupporting
confidence: 91%
“…4 B) but less in a contraction with stretching than one with shortening. These results were similar to those of Fenn ( 1924 ) and Fick ( 1881 ). Whereas those authors had concluded that the results indicated that physiological processes accounted for the heat and work output, Wyman produced what now appear rather contrived arguments—a variable fraction of potential elastic energy not used as work was reabsorbed during relaxation rather than appearing as heat—to support the idea that all the thermal changes could be explained by processes that were physical (i.e.…”
Section: Consequences Of Fenn’s Papersupporting
confidence: 91%
“…Since its first description at the end of the 19th century (Fick, 1881), eccentric exercise has sparked much interest on account of distinctive features enabling high external mechanical power at reduced cost and its potential for positive rehabilitation and training outcomes (Hoppeler, 2016).…”
Section: Introductionmentioning
confidence: 99%